La resémantisation de la ligne frontière dans des régions métropolitaines transfrontalières : le Jardin des 2 Rives à Strasbourg et la place Jacques Delors à Lille - Bernard Reitel; François Moullé (Belgeo)
This article focuses on the way public bodies have invested borders in the European Union and especially how some parts of the limit of sovereignty are transformed into cross-border places in the process of construction of cross-border metropolitan regions. These places, binding two national territories instead of separating or distancing, are the results of cooperation’s projects between territorial authorities on local level. Two projects are analysed: the Garden of the Two Banks in Strasbourg and Kehl between France and Germany achieved in 2004 and the Jacques Delorsplein in Menen and Halluin between Belgium and France, created in 2014.In the first case, the border spaces located on both sides of the Rhine river were regenerated and transformed into a common cross-border recreation and leisure area whose symbolic heart is a pedestrian and bicycle bridge. In the second case, the margin spaces located on the borders between two neighboured municipalities became a public square. The genesis and the reasons of the creation of these two spaces are different, but the comparison is quite relevant considering their transformations into public spaces, their symbolic meaning and the need of cross-border cooperation to ensure the urban management. The ‘refoundation’ of the border area is due to a change of the functions and more deeply in the transformation of its meaning inside the urban area, enabling new people’s space practices. The transformation of the border from articulation or interface to a living space is both the results of cross-border governance and a innovating answer to issues regarded as being similar by the public bodies. The metropolitan context enables to get resources necessary to build the basis of a cooperation and to produce a place in the ‘urban semic system’ which is constructed at cross-border urban scale. The appropriation of these two spaces by the people is still very different. The Garden of the Two Banks is a popular public space in the cross-border urban area of Strasbourg-Kehl while the Jacques Delors square is only the starting point of a regenerated area project.